The discrepancy between patient expectations and actual outcome reduces at the first 6 months following total knee replacement surgery - Levinger, P.; Bartlett, J.; Bergman, N.; McMahon, S.; Menz, H.; Hill, Keith (Springer, 2018)
Purpose: Patients undergoing total knee arthroplasty often have unfulfilled expectations from the surgery that can lead to dissatisfaction. This study aimed to examine the discrepancy between patients’ expectations and actual functional abilities prior to undergoing knee replacement surgery, and at 6 and 12 months following the surgery. Methods: A survey was undertaken of patients before, and 6 and 12 months post-surgery. The survey included the Knee Surgery Perception Questionnaire (KSPQ) to assess patients’ current perception of their level of function and pain, their desired outcomes, and the discrepancy between the two. Pain, function and quality of life were also assessed. Repeated measure ANOVAs were used to assess differences between pre- and post-surgery. Results: A total of 176 patients were surveyed. Significant differences in the KSPQ discrepancy scores (subscale and total scores) were demonstrated between the three assessment point times (p < 0.01). Paired t tests identified significant differences between the pre-surgery and 6-month KSPQ discrepancy scores, (p < 0.01) indicative of substantial improvement in physical function and slight reduction in expectations. Overall significant improvement (p < 0.01) was reported over time across all measures: physical function, pain and stiffness and quality of life. Conclusion: The discrepancy between patients’ current abilities and their expectation changes following surgery, especially in the first 6 months post-surgery. Patients’ goals might change as their function and pain improve post-surgery. Combining education programmes and discussion with the treating orthopaedic surgeons pre-operatively is important for the development of realistic, achievable expectations. Level of evidence: III.